The Evaluation of Microplastic Reduction in Biofloc Aquaculture for Sustainable Nile Tilapia Cultivation - Deswati, Deswati; Zein, Rahmiana; Novsimapera, Gatri; Putra, Adewirli (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Sustainable aquaculture requires environments free from microplastic contamination. However, microplastics are now commonly found in aquatic systems, including fish farms, where they can accumulate in organisms and enter the food chain. This study evaluates the effectiveness of biofloc technology in reducing microplastic levels in water and Nile tilapia (Oreochromis niloticus), using ecological risk indices: Pollution Hazard Index (PHI), Pollution Load Index (PLI), and Potential Ecological Risk Index (PERI). The experiment lasted 50 days with four treatments, including polyethylene (PE) and polyethylene terephthalate (PET) exposure. Microplastic concentrations ranged from 0.12 to 0.33 particles/L, with highest accumulation in the fish esophagus (39.2 ± 6.87 particles/g). Identified polymers included PE, PVC, and PA. Risk indices showed PHI = 166.69, PLI = 1.01–1.66, and PERI = 21.49, indicating medium to high ecological risks. Results show that biofloc effectively reduces microplastic levels, making it a promising solution for sustainable aquaculture. The study highlights the need for better plastic waste management policies and stricter regulation of PVC and PET near farming areas.